From Trust to Loyalty: Examining Media Credibility, Influencers, and Social Media Marketing in Nike Ciputra Consumers on Semarang City (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the influence of media credibility, influencers, and social media marketing on brand loyalty, with brand trust as a mediating variable, focusing on Nike Ciputra Semarang consumers. Grounded in Signaling Theory and Attribution Theory, the research explains how credible and consistent signals from media and influencers foster trust, which in turn strengthens brand loyalty. A quantitative approach was employed through questionnaires distributed via Google Forms, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that media credibility, influencers, and social media marketing positively affect brand loyalty, while brand trust significantly mediates these relationships. The findings support the Signaling Theory and Attribution Theory,highlighting the role of external digital communication stimuli in building trust and driving loyalty. This study contributes practical insights for businesses and digital marketers on the importance of trust-based strategies in enhancing customer loyalty.
Keywords: Media Credibility, Influencer; Social Media Marketing; Brand Trust; Brand Loyalty